Role of a multidisciplinary team approach in the management of chronic thromboembolic pulmonary hypertensionCentral MessagePerspective - Benjamin Yang, MD; Anthony Zaki, MD; Nicholas Oh, MD; Juan Umana-Pizano, MD; Ihab Haddadin, MD; Alice Goyanes, MD; Nicholas Smedira, MD, MBA; Haytham Elgharably, MD; Michael Zhen-Yu Tong, MD, MBA; Gustavo A. Heresi, MD, MS (JTCVS Open)
Objective: Chronic thromboembolic pulmonary hypertension (CTEPH) is an under-recognized complication of pulmonary embolism that, if left untreated, leads to heart failure. This study aimed to characterize the role of a multidisciplinary team in the management of CTEPH. Methods: Starting in 2011, a multidisciplinary team was assembled to systematically evaluate and manage all CTEPH patients based on hemodynamic profile, extent of thromboembolic disease burden, and comorbidities. From 1997 to 2021, 306 patients underwent pulmonary thromboendarterectomy for CTEPH. The cohort was divided into an early era prior to 2011 (62 cases) and a recent era from 20,211 to 2021 (244 cases). Results: Baseline demographic and hemodynamic profiles were similar in the 2 eras, with a mean age of 53 ± 14 years, mean pulmonary artery pressure of 44.9 ± 11.2 mm Hg, and mean pulmonary vascular resistance of 7.4 ± 3.9 Wood units. Early era patients had more severe right ventricular dysfunction (49.1% vs 25.0%; P < .001). Recent era patients underwent more concomitant tricuspid valve repairs (22% vs 2.9%; P < .001) despite similar tricuspid regurgitation severity. Following surgery, recent era patients had lower in-hospital mortality (2.9% vs 12%) with less morbidity, including less prolonged ventilation (32% vs 59%), less need for dialysis (1.6% vs 21%), and shorter hospital length of stay (16 days vs 21 days). The difference in survival was sustained long-term (88% vs 70% at 6 years). Conclusions: Outcomes after pulmonary thromboendarterectomy improved since the establishment of the multidisciplinary team—most notably, more complete resolution of pulmonary hypertension and improved overall survival. A team-based approach for selection and perioperative management of these complex patients can be associated with improved early outcomes.